New insights to understand the influence of hairy vetch on maize yield and its response to nitrogen application - Cafaro La Menza, Francisco; Salvagiotti, Fernando; Maltese, Nicolás; Eclesia, Roxana Paola; Barraco, Miriam Raquel; Echarte, Laura; Barbieri, Pablo; Carciocchi, Walter Daniel (Elsevier, 2025)
Including hairy vetch (Vicia villosa Roth.) in a crop sequence before maize (Zea mays L.) can enhance the cash crop grain yield and reduce nitrogen (N) fertilizer needs, though the effects are inconsistent. This study aimed to identify the variables influencing maize grain yield response to hairy vetch as a preceding cover crop and N fertilization in maize following hairy vetch. We conducted 70 experiments evaluating four treatments resulting from the inclusion (or not) of hairy vetch previous to maize with and without subsequent N fertilization. Our findings revealed significant (p<0.05) positive response of maize to hairy vetch in 21 % of the experiments (average increase of 2.79 t ha−1) and yield reductions in 13 % (average decrease of −2.02 t ha−1). The magnitude of this response was explained by the N-limited yield index (ratio between N-fertilized and non-N fertilized maize yield), N contribution from vetch, water balance of the whole sequence, and management practices of both crops (e.g., sowing dates and hairy vetch cycle length). Maize grain yield following hairy vetch showed positive response to N application in 27 % of the experiments (average of 2.68 t ha−1). Positive responses to N fertilization were evident in environments with a high N-limited yield index, low N contribution from hairy vetch, favorable water availability, and low soil organic matter concentration. These findings provide valuable insights for producers seeking to optimize the use of hairy vetch to reduce reliance on synthetic fertilizers on succeeding maize crop, ultimately contributing to more sustainable and diversified cropping systems.